Resilience of SMEs in Facing Economic Crises: Business Model Adaptation, Product Diversification, and Resource Optimization - Jayanto, Imam; Anggraeni, Inda Permata; Safitransyah, Rahmad Puja (PT. LITERASI SAINS NUSANTARA, 2025)
SMEs play a strategic role in the economy but are highly vulnerable to economic crises. This study aims to analyze SME resilience strategies in navigating economic downturns through business model adaptation, product diversification, and resource optimization. Using a literature review approach with qualitative methods and descriptive analysis, data were collected from Google Scholar and other credible sources for the period 1957–2025. From the initial 50 articles identified, a rigorous selection process resulted in 34 relevant articles. The findings indicate that SMEs capable of adjusting their business models to market dynamics have a higher chance of survival. Product diversification has been proven effective in reducing business risks, while resource optimization enhances operational efficiency and competitiveness. The theories of Organizational Resilience, Business Model Canvas, and Resource-Based View serve as the foundation for understanding the factors influencing SME resilience. Case studies demonstrate that Indonesian SMEs adopting digital innovations and adaptive strategies perform better in times of crisis. This study provides implications for business practitioners, policymakers, and academics in designing more adaptive strategies to enhance SME sustainability.